Psychology in Times of Crisis An economic psychological analysis of the coronavirus pandemic - Kirchler, Erich; Pitters, Julia; Kastlunger, Barbara (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
When the SARS-CoV-2 virus reached us in Europe, we panicked. Life was scaled down to the bare essentials and tentatively loosened up again. The lockdown is followed by huge changes. There is no return to familiar normality in sight. How did we experience the threat to our health and the changes to the familiar rituals of life? What followed shock and fear? How did we manage to discard long-rehearsed rituals and accept the challenges? How will we talk about the policies after the lockdown, what will we remember and what will we have learned from the crisis? This Essential offers an economic psychological analysis of the complex interplay between state, organisations and people from the beginning of the crisis to the repair phase. The content Corona crisis from an economic psychology perspective Onset of the crisis at micro, meso and macro level Living in the crisis at micro, meso and macro level Repair and retrospection The target groups Entrepreneurs, self-employed, political scientists, psychologists, sociologists, economists, economists Students of all social sciences The authors Erich Kirchler is Professor of Economic Psychology at the University of Vienna. Julia Pitters is Professor of Economic Psychology at the International University of Applied Sciences IU, Bad Reichenhall. Barbara Kastlunger is Professor of Economic Psychology at the DBU Digital Business University of Applied Sciences, Berlin.
Chronology of events -- Beginning of the crisis -- Life in times of crisis -- Repair, hindsight and outlook.
Keywords: Economics-Psychological aspects; Social psychology; Public administration; Economic Psychology; Social Psychology; Public Management